The Market for Corporate Assets: Who Engages in Mergers and Asset Sales and Are There Efficiency Gains? - Maksimovic, Vojislav; Phillips, Gordon (Journal of Finance, 2001)
ABSTRACT We analyze the market for corporate assets. There is an active market for corporate assets, with close to seven percent of plants changing ownership annually through mergers, acquisitions, and asset sales in peak expansion years. The probability of asset sales and whole‐firm transactions is related to firm organization and ex ante efficiency of buyers and sellers. The timing of sales and the pattern of efficiency gains suggests that the transactions that occur, especially through asset sales of plants and divisions, tend to improve the allocation of resources and are consistent with a simple neoclassical model of profit maximizing by firms.